Vitamin D Metabolite, 25-Hydroxyvitamin D, Regulates Lipid Metabolism by Inducing Degradation of SREBP/SCAP. Issue 2 (16th February 2017) - Asano, Lisa; Watanabe, Mizuki; Ryoden, Yuta; Usuda, Kousuke; Yamaguchi, Takuya; Khambu, Bilon; Takashima, Megumi; Sato, Shin-ichi; Sakai, Juro; Nagasawa, Kazuo; Uesugi, Motonari
Summary: Sterol regulatory element-binding proteins (SREBPs) are transcription factors that control lipid homeostasis. SREBP activation is regulated by a negative feedback loop in which sterols bind to SREBP cleavage-activating protein (SCAP), an escort protein essential for SREBP activation, or to insulin-induced genes (Insigs) (endoplasmic reticulum [ER] anchor proteins), sequestering the SREBP-SCAP-Insig complex in the ER. We screened a chemical library of endogenous molecules and identified 25-hydroxyvitamin D (25OHD) as an inhibitor of SREBP activation. Unlike sterols and other SREBP inhibitors, 25OHD impairs SREBP activation by inducing proteolytic processing and ubiquitin-mediated degradation of SCAP, thereby decreasing SREBP levels independently of the vitamin D receptor. Vitamin D supplementation has been proposed to reduce the risk of metabolic diseases, but the mechanisms are unknown. The present results suggest a previously unrecognized molecular mechanism of vitamin D-mediated lipid control that might be useful in the treatment of metabolic diseases. Graphical Abstract: Highlights: 25-Hydroxyvitamin D (25OHD) is an endogenous inhibitor of SREBP 25OHD induces proteolytic processing and ubiquitin-mediated degradation of SCAP The mechanism provides a potential therapeutic approach for lipid disorders Abstract : Asano et al. identified 25-hydroxyvitamin D (25OHD) as a new endogenous inhibitor of SREBP. 25OHD impairs SREBP activation by inducing proteolytic processing and ubiquitin-mediated degradation of SCAP, implying a new opportunity for pharmacological control of SREBP/SCAP.